2016
DOI: 10.5121/ijait.2016.6102
|View full text |Cite
|
Sign up to set email alerts
|

Change Management: Implementation and Benefits of The Change Control in the Information Technology Environment

Abstract: In the competitive environment, companies have given increasing importance to the IT sector and the resources it delivers as strategic. As a result, IT becomes a living being within the company. This sector is being subject to continuous changes in this scenario. These changes can occur within the own IT sector or whether IT to other sectors of the company. For both scenarios, it is important to have a good change control to avoid unnecessary trouble and expense. This paper aims to show through a case study, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…HSP ITIL implementation project manager found that combining ITIL with other service quality and governance standards such as ISO standards, COBIT framework and Balance Score Cards have contributed to the project success. [43] suggested that COBIT and BAI06 is an essential combination for change management process.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…HSP ITIL implementation project manager found that combining ITIL with other service quality and governance standards such as ISO standards, COBIT framework and Balance Score Cards have contributed to the project success. [43] suggested that COBIT and BAI06 is an essential combination for change management process.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The ITIL-based Multidimensional Incident Analytics Method is discussed by some researchers (Saarelainen & Jäntti, 2015). This paper (de Andrade et al, 2016) aims to demonstrate the advantages and outcomes of implementing a process for managing and controlling changes in the information technology environment of a large Brazilian government company through a case study. The implementation process was motivated by the following anticipated benefits: the improved connection between IT services and business by exercising greater control over the implementation of the changes, greater visibility into the changes, a reduction in the negative impact of the changes, a better assessment of the cost-benefit ratio of the change prior to its implementation, a reduction in cost, time, and rework, more stable services, and an increase in user productivity.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Andrade & Abuguergue et al (2016) adds that implementation of the change management process is not complicated, but you should not expect its implementation from day to night. There is need to adapt the process to the culture and maturity of the company, requiring dedication, commitment and effort of everyone involved, so that we can break resistance and paradigms related to change with the use of the process (Andrade et al, (2016). Jaros (2010) argues that in order for organizations to not just survive but prosper, they must be knowledgeable about 'how to implement appropriate organizational changes that will be embraced by their employees' unfortunately, successful organizational change efforts are 'rare', with most failing to fulfill their promise.…”
Section: Implementation Of Changementioning
confidence: 99%